2016
DOI: 10.1016/j.vaccine.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Newcastle disease virus expressing H9 HA protects chickens against heterologous avian influenza H9N2 virus challenge

Abstract: In order to produce an efficient poultry H9 avian influenza vaccine that provides cross-protection against multiple H9 lineages, two Newcastle Disease Virus (NDV) LaSota vaccine strain recombinant viruses were generated using reverse genetics. The recombinant NDV-H9Con virus expresses a consensus-H9 hemagglutinin (HA) that is designed based on available H9N2 sequences from Chinese and Middle Eastern isolates. The recombinant NDV-H9Chi virus expresses a chimeric-H9 HA in which the H9 ectodomain of A/Guinea Fowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…While antigenically matched vaccines can provide good protection against clinical signs of disease and reduce viral shedding, this protection does not extend to less genetically related isolates of the same subtype and does not prevent infection of other AIV subtypes [92]. Many countries where H9N2 is endemic have been using vaccination as a control method, but many still see outbreaks resulting from H9N2 AIVs [93]. New vaccine developments are working on reducing the cost and difficulty of production of current inactivated vaccines while also increasing the efficacy and providing broader protection against multiple H9N2 subtypes.…”
Section: H9n2 Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…While antigenically matched vaccines can provide good protection against clinical signs of disease and reduce viral shedding, this protection does not extend to less genetically related isolates of the same subtype and does not prevent infection of other AIV subtypes [92]. Many countries where H9N2 is endemic have been using vaccination as a control method, but many still see outbreaks resulting from H9N2 AIVs [93]. New vaccine developments are working on reducing the cost and difficulty of production of current inactivated vaccines while also increasing the efficacy and providing broader protection against multiple H9N2 subtypes.…”
Section: H9n2 Preventionmentioning
confidence: 99%
“…Intranasal immunization of ferrets with VLPs containing H5, H7, and H9 proteins significantly reduced viral load after challenge with three AIVs including an H9N2 human origin isolate (human/HK/33984/2009 [94]. A recombinant Newcastle Disease virus (NDV) H9 vaccine that expressed multiple H9N2 HA was successful in protecting against heterologous H9N2 viruses in chickens [93]. Reduction of viral shedding and elimination of clinical signs post challenge was achieved although genetic differences between the vaccine HA and the challenge strain were still impactful with less protection from a more distantly related isolate [93].…”
Section: H9n2 Preventionmentioning
confidence: 99%
“…In a subsequent paper we showed that the H3-con and H5-con antigens were also immunogenic and could provide cross-protective immunity against multiple heterologous lethal influenza challenges when delivered individually 4 . While our study focuses on more human relevant influenza subtypes, others have applied this approach to avian influenza viruses with potential for zoonotic transmission such as avian H5N1, H7N9 and H9N2 26 , 30 , 31 . Unfortunately, we are unable to test if the H2-con gene induced any protection at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Newcastle disease virus (NDV) is a promising vector for live vaccine development due to some advantages, including a high virus yield in embryonated chicken eggs, an induction of robust humoral and cellular immunity, and the potential for mass administration via drinking water or aerosol spray. Avirulent NDV strains have been used as vectors to express hemagglutinin (HA) of H9N2 subtype AIVs, and these vaccines are generally immunogenic and efficacious in chickens [9,10]. However, the maternal Newcastle disease (ND) antibodies present in commercial chickens severely interfere with the replication of the vectored vaccine viruses and thus impair the efficacy of this kind of vaccine [11,12].…”
mentioning
confidence: 99%
“…Vaccination is considered as one of the principal strategies for controlling H9N2 AI. Previous report showed that recombinant NDV-vectored vaccine candidates conferred protection against H9N2 AIVs infection in chickens [9,10]. However, owing to the interference of the maternal ND antibodies acquired by intensive ND vaccination in commercial poultry flocks, vaccination failure is often seen when live ND vaccines or NDV-vectored vaccines are administered in young chickens.…”
mentioning
confidence: 99%